2017
DOI: 10.1021/acsami.7b02823
|View full text |Cite
|
Sign up to set email alerts
|

Functional Paper-Based Platform for Rapid Capture and Detection of CeO2 Nanoparticles

Abstract: Development of systems for capture, sequestration, and tracking of nanoparticles (NPs) is becoming a significant focus in many aspects of nanotechnology and environmental research. These systems enable a broad range of applications for evaluating concentration, distribution, and effects of NPs for environmental, clinical, epidemiological, and occupational exposure studies. Herein, we describe the first example of a ligand-graft multifunctional platform for capture and detection of cerium oxide (CeO or ceria) N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…This confirms the ability of both vitamin C and E to fight the oxidative damage results from ZnONP exposure. Our results were confirmed by previous observations; recently, vitamin C has been used to prepare a ligand for cerium oxide NPs as promising tool for facilitating NP detections in tissues [ 57 ]. This explained how much it has the power for binding of NPs; this illustrated the efficacy of vitamin C to tight bind to NPs and do its action.…”
Section: Discussionsupporting
confidence: 91%
“…This confirms the ability of both vitamin C and E to fight the oxidative damage results from ZnONP exposure. Our results were confirmed by previous observations; recently, vitamin C has been used to prepare a ligand for cerium oxide NPs as promising tool for facilitating NP detections in tissues [ 57 ]. This explained how much it has the power for binding of NPs; this illustrated the efficacy of vitamin C to tight bind to NPs and do its action.…”
Section: Discussionsupporting
confidence: 91%
“…This ability of VCs to combat possible oxidative damage was caused by exposure to Cu-NPs. Othman et al (2017) explained that they used VC to prepare ligands for cerium oxide nanoparticles as a tool to facilitate the detection of NP in tissues because they suggested that VC could bind tightly to NPs and showed its performance. It has also been reported that the presence of NPs themselves can increase the VC activity (Astete et al 2011).…”
Section: )mentioning
confidence: 99%
“…Deconvoluted peaks were used for calculating the concentration of Ce 3+ . The Ce 3d spectrum (Figure ) of Ce NCs shows the spin orbit doublets for pure ceria, 3d 3/2 and 3d 5/2 with binding energy peaks at 882 and 903 eV corresponding to the Ce 3+ oxidation state, and peaks at 879, 896, and 912 eV corresponding to the Ce 4+ oxidation state. This result clearly indicates the presence of mixed oxidation states of Ce 3+ and Ce 4+ species on the NC’s surface. Similar peak fitting was also done for the XPS of Ce doped with Eu 3+ (Figure ).…”
Section: Results and Discussionmentioning
confidence: 97%